Enhancing Students’ Mobile-Assisted Language Learning through Self-Assessment in a Chinese College EFL Context - Pingping, Guo; Qiuyao, Wang; Linyan, Bao (Journal of Education and e-Learning Research, 2021)
The rapid development of mobile communication technology, high penetration of mobile devices as well as the increasing number of mobile English learning applications all together facilitate the feasibility and popularity of mobile-assisted English learning among Chinese college students. Self-assessment is always recommended as a powerful strategy to enhance learning by helping learners regulate their study and improve their motivation and engagement, so it may also offer the potential to evaluate students’ mobile autonomous learning in the new era. This study investigates the current condition of Chinese college students’ mobile-assisted English learning, and which self-assessment strategies are employed during the process. Data collected from the questionnaire, which surveyed about 300 undergraduates from 7 Chinese public and private universities, show the popularity of mobile-assisted English learning among Chinese undergraduates. However, in terms of self-assessment strategies, the results are less optimistic, for only about half of the respondents use it with a medium to high frequency. The reasons, analyzed through a follow-up interview, mainly lie in the lack of strong will and motivation, the loneliness of learning alone and the difficulty in finding the perfect application. Suggestions for strengthening self-assessment include improving knowledge of what self-assessment is and its benefits, planning one’s study properly, improving collaboration with classmates, involving teachers as supporters and paying more attention to subsequent reflection.